Size distribution and lung‐deposited doses of particulate matter from household exposure to biomass smoke. (29th July 2020) - Nicolaou, Laura; Fandiño‐Del‐Rio, Magdalena; Koehler, Kirsten; Checkley, William
Abstract: Exposure to high concentrations of particulate matter (PM) is associated with a number of adverse health effects. However, it is unclear which aspects of PM are most hazardous, and a better understanding of particle sizes and personal exposure is needed. We characterized particle size distribution (PSD) from biomass‐related pollution and assessed total and regional lung‐deposited doses using multiple‐path deposition modeling. Gravimetric measurements of kitchen and personal PM2.5 (<2.5 µm in size) exposures were collected in 180 households in rural Puno, Peru. Direct‐reading measurements of number concentrations were collected in a subset of 20 kitchens for particles 0.3‐25 µm, and the continuous PSD was derived using a nonlinear least‐squares method. Mean daily PM2.5 kitchen concentration and personal exposure was 1205 ± 942 µg/m 3 and 115 ± 167 µg/m 3, respectively, and the mean mass concentration consisted of a primary accumulation mode at 0.21 µm and a secondary coarse mode at 3.17 µm. Mean daily lung‐deposited surface area (LDSA) and LDSA during cooking were 1009.6 ± 1469.8 µm 2 /cm 3 and 10, 552.5 ± 8261.6 µm 2 /cm 3, respectively. This study presents unique data regarding lung deposition of biomass smoke that could serve as a reference for future studies and provides a novel, more biologically relevant metric for exposure‐response analysis compared to traditional size‐based metrics.